Booderee National Park Management: Connecting science and management. (28th January 2013) - Lindenmayer, David B.; MacGregor, Christopher; Dexter, Nick; Fortescue, Martin; Cochrane, Peter
<x xml:space="preserve">Abstract</x> A 10‐year science–management partnership has focussed on three key issues within Booderee National Park in eastern Australia: the impacts of fire on native biota, the response of vertebrates to feral animal control and the control of Bitou Bush. What has been achieved to date and what are the partnership's key ingredients?